¿Qué es el matrimonio? - Sherif Girgis; Robert P. George; Ryan T. Anderson (Universidad Hemisferios, 2020)
Here is studied mainly what marriage is. By the way, the analysis shows how this debate has profound consequences in the common good and how its protection should be regulated. With a systematically method, authors review the most important opinions about marriage, for and against the usual notion, and then they weigh their consistency. The analysis is divided into two parts. In the first one is defined the notion of the authentic marriage and the consequences that it has on the common good (consequences that justify the State’s actions in this matter). There are analyzed all kinds of romantic unions, monogamous or not, taking care of the public interest that they can present. Part II considers all of the serious concerns that are not treated earlier: the objections from conservatism (Why not spread traditional norms to the gay community?), from practicality (What about partners’ concrete needs?), from fairness (Doesn’t the conjugal conception of marriage sacrifice some people’s fulfillment for others’?), from naturalness (Isn’t it only natural?), and from neutrality (Doesnʹt traditional marriage law impose controversial moral and religious views on everyone?). The main conclusion is that marriage understood as the conjugal union of man and woman really serves for the good of the children, the good of the spouses, and the common good of the society; these benefits do not occur in the same way in same sex marriage.